One important factor for development and water resources management is analysis discharge the availability of water.Information about the availability of water can be used for various needs, of them to analyze discharge the availability of water, beforeha - Pratiwi, Bertha Silvia (Semarang State University, 2014)
One important factor for development and water resources management is analysis discharge the availability of water.Information about the availability of water can be used for various needs, of them to analyze discharge the availability of water, beforehand kinds of analysese of precipitation data with an analysis of potential evapotranspiration. Flow characteristic Methods and methods of the year the basis of planning ( basic year ) is a step in an analysis discharge andalan (Q80 ).Both of these methods in comparation to determine the amount of water availability in accordance with the state of the watershed of this study. Basic Year which was the year that the reliability of data debit have 80 % ( Q80 ), that is because the risks facing debit of less than discharge mainstay of about 20 % of the number of observationsSalah satu faktor penting untuk pengembangan dan pengelolaan sumber daya air adalah analisis debit ketersediaan air. Informasi mengenai ketersediaan air dapat dimanfaatkan untuk berbagai kebutuhan, diantaranya untuk menganalisis debit ketersediaan air, terlebih dahulu dilakukan analisis data curah hujan dengan analisis evapotranspirasi potensial. Methode flow characteristic dan Metode Tahun Dasar Perencanaan (Basic Year) adalah langkah dalam analisa debit andalan (Q80). Kedua metode tersebut di comparasi untuk menentukan besaran ketersediaan air yang sesuai dengan keadaan DAS studi ini. Tahun dasar yang dipakai adalah tahun yang data debitnya mempunyai keandalan 80% (Q80), yaitu resiko yang dihadapi karena terjadi debit kurang dari debit andalan sebesar 20 % dari jumlah pengamatan.Â